Comparison of empirical structural vulnerability rapid prediction models considering typical earthquakes. (March 2023) - Li, Si-Qi
Abstract: The damage caused by different destructive earthquakes to various building structures has diverse characteristics. To understand the failure mode and vulnerability mechanism of various structures under a typical destructive earthquake, a relatively accurate rapid prediction model suitable for the vulnerability of various specific structures is constructed. In the present study, four distinct structural typologies of the Wenchuan earthquake (Dujiangyan city) and Jiuzhaigou earthquake (Jiuzhaigou county) in China are examined, and the failure characteristics and damage mechanism are studied. A rapid vulnerability prediction method based on multidimensional parameters is proposed. The model is verified using the established structural vulnerability database (8, 553 buildings). The comparison models of rapid vulnerability prediction of various typical structures (surface, function, and matrix) are developed. A new method for the rapid prediction of regional group structure vulnerability based on resultant peak acceleration parameters is proposed, and a quantitative relationship model based on resultant peak acceleration and macrointensity level is constructed. The traditional vulnerability index calculation model is modified and improved, and a new fragility rapid prediction model of regional typical structural groups based on the revised average earthquake damage index parameter is obtained. Using the verification of the empirical structure seismic damage sample database of field inspection, the established multidimensional vulnerability rapid prediction model of typical structures has greater stability and reliability.